2006
DOI: 10.1143/jjap.45.l790
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Polymer Light-Emitting Diode Performance Using Polymer Heterojunction Structure Prepared by Evaporative Spray Deposition from Ultradilute Solution

Abstract: We successfully demonstrated a significant improvement in polymer light-emitting diode performance by employing a polymer bilayer structure prepared by evaporative spray deposition from ultradilute solution (ESDUS). The bilayer structure consisted of two -conjugated polymers, where the top layer was deposited from tetrahydrofuran (THF) solution by ESDUS onto the preceding bottom layer composed of the other THF-soluble polymer. The external quantum efficiency (EQE) of the bilayer device is improved markedly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…When displays are in question, it is very popular to consider flat panel ones and more concrete the promising organic based displays. In contrast to the epitaxial growth of single crystal inorganic electroluminescent semiconductors, organic electroluminescent films are easy for deposition via cheap techniques like spin-coating, spray deposition and ink-jet printing [1,2],. Nowadays, a tendency to make the displays thinner and lighter, and to replace conventional paper with "electronic paper", by using of flexible substrates is imposed.…”
Section: Introductionmentioning
confidence: 99%
“…When displays are in question, it is very popular to consider flat panel ones and more concrete the promising organic based displays. In contrast to the epitaxial growth of single crystal inorganic electroluminescent semiconductors, organic electroluminescent films are easy for deposition via cheap techniques like spin-coating, spray deposition and ink-jet printing [1,2],. Nowadays, a tendency to make the displays thinner and lighter, and to replace conventional paper with "electronic paper", by using of flexible substrates is imposed.…”
Section: Introductionmentioning
confidence: 99%
“…8) In addition, an efficient high-speed organic photoconductive device has been demonstrated using a multilayer structure composed of donor-acceptor alternating layer. 9) Most of organic materials, particularly polymers, can only be prepared by using solution processes, such as a dipcoating, 10) a spray deposition, 11) and a conventional spincoating. One serious problem of the solution process is the solvent and dust residues remained into an organic layer.…”
Section: Introductionmentioning
confidence: 99%
“…The evaporative spray deposition using ultradilute solution (ESDUS) technique is a polymer thin film preparation method having significant four advantageous features; 1) non-vacuum process, 2) pixel size deposition with simple shadow masks, 3) device fabrication of polymers showing very low solubility, 4) layer-by-layer deposition of polymers soluble to a same solvent. Recently we demonstrated that polymer light-emitting diodes (PLEDs) with a polymer stacking layered structure were fabricated by ESDUS, resulting drastic improvement in the device performance [1][2][3].…”
Section: Introductionmentioning
confidence: 99%